Expectations Come True: The Placebo Effect of Exercise on Affective Responses - Wang, Yu-Bu; Guo, Lu; Fan, Jun-Yi; Mao, Zhi-Xiong (Research quarterly for exercise and sport, 2023)
Objective: This study investigated the placebo and nocebo effects of habitual and induced expectations. Methods: In Study 1, 95 participants (M age = 19.65 ± 2.21 years, M BMI = 21.94 ± 2.55) were grouped according to habitual expectations (positive, neutral, or negative) and completed a 30-min moderate-intensity aerobic exercise, and their affective response, rating of perceived exertion (RPE), and heart rate variability (HRV) were measured before, during, and after the exercise. In Study 2, the participants from Study 1 were grouped according to induced expectations (control, positive, or negative) and completed a 30-min moderate-intensity aerobic exercise. Affective response, RPE, and HRV were measured before, during, and after exercise. Results: In Study 1, positive habitual expectations increased affective response during and after exercise [F(2, 92) = 2.959, p = .057, η p 2 = .060], and negative habitual expectations increased RPE during exercise [F(2, 92) = 5.174, p = .007, η p 2 = .101]. In Study 2, positive induced expectation increased affective response during [F(2, 86) = 5.492, p = .006, η p 2 = .113] and after exercise [F(2, 86) = 6.096, p = .003, η p 2 = .124] and was not affected by habitual expectation. Conclusion: The affective response during and after exercise is influenced by habitual and induced expectations. Positive expectations enhance affective benefits, while negative expectations reduce affective benefits.